TARGETING NUCLEAR FACTOR KAPPA B WITH CHELATED ZINC COMPOUNDS TOWARDS ANTICANCER DRUG DESIGN - K., NAGALAKSHMI; S., SHILA; L., INBATHAMIZH; A., THENMOZHI; P., RASAPPAN; P. T., SRINIVASAN (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of the study was to analyse the target-ligand interactions between nuclear factor-κB (NF-κB) and chelated Zinc compounds and to explore the anticancer drug potential of these ligands by a bio computational approach. Methods: Bioinformatics databases and tools were applied for the study. Three dimensional structure of the target NF-κB was retrieved from Protein Data Bank (PDB). The optimized structures of two chelated Zinc compounds, Zinc acetate and Zinc orotate were taken for docking studies with the target using docking tool AutoDock 4.2. Drug properties of the ligands were further assessed by Molinspiration server. Results: Docking results as predicted by AutoDock and as visualized by PyMol viewer were effective for both the ligands. Comparatively, Zinc orotate showed minimum energy and more interactions with the target. Both the ligands satisfied the Lipinski’s rule of five with zero violations. Conclusion: The findings emphasized the promising role of chelated Zinc compounds as potent drug candidates in anti-cancer drug design against NF-κB.